1991
DOI: 10.1287/mnsc.37.10.1221
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Bargaining with Transaction Costs

Abstract: A buyer and seller alternate making offers until an offer is accepted or someone terminates negotiations. The seller's valuation is common knowledge, but the buyer's valuation is known only by the buyer. Impatience to reach an agreement comes from two sources: the traders discount future payoffs and there are transaction costs of bargaining. Equilibrium behavior involves either immediate trade, delayed trade, or immediate termination, depending on the size of the gains from trade and the relative bargaining co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Time pressure exists for all goods and services since if it does not matter when the good or service is sold, it would not matter whether they were sold at all (Cramton, 1991). The degree of time pressure, however, can differ among different goods and services.…”
Section: Influencing Aspectsmentioning
confidence: 99%
“…Time pressure exists for all goods and services since if it does not matter when the good or service is sold, it would not matter whether they were sold at all (Cramton, 1991). The degree of time pressure, however, can differ among different goods and services.…”
Section: Influencing Aspectsmentioning
confidence: 99%
“…The expected profits under the sequential BA are given by Eqs. (5) and (6). The expected profits under the option mechanism are given by Eqs.…”
Section: Comparison Of Expected Profitsmentioning
confidence: 99%
“…Later, Rubin and Carter (1990) demonstrated that Banerjee's work can be generalized to a variety of goods and services and showed that compromises by the buyer and the supplier result in improved protability for both. Cramton (1991) proposed a bargaining model with transaction costs between a buyer and a supplier. He suggests that in the state of equilibrium an immediate trade, delayed trade, or immediate termination occurs depending on the size of the gains from trade and relative bargaining costs.…”
Section: Analytical Modelsmentioning
confidence: 99%